Smart Green Garden - Baraa Sawafta; Mahmoud Kazlak (My University, 2024)
This project is pivotal due to its potential to revolutionize waste management practices, addressing a critical issue faced by many communities. The importance of the project lies in its ability to save human resources, enhance efficiency, and contribute to cleaner and healthier spaces. The WasteCar is a waste car that can be directed to move in different directions using a remote control. The remote control is programmed with specific buttons to manage the WasteCar’s movements and operations. One button controls the arm of the WasteCar, allowing it to lower to the ground, pick up waste, and place it in the basket. Another button is programmed to empty the basket by tilting it backward three times to ensure all trash is expelled. The main objectives of the project revolve around reducing the dependence on manual labor for waste collection, promoting sustainable practices through efficient waste handling, and adapting to different environments. The methodology employed in the application development process encompasses a thorough design phase, testing procedures, and continuous refinement to ensure the robot's reliability and effectiveness in diverse real-world scenarios.
TrainLink